(untitled) (Tokyo, 1977)
This book introduce eyewitnesses of history, climate of Japan, seas around Japan, mountains of Japan, volcanoes of Japan, plains of Japan, genealogy of Japanese people, made-over nature of Japan, early life of the Japanese islands.
Keywords: Lịch sử tự nhiên,Natural history; Nhật Bản,Japan